2023
DOI: 10.1007/s40430-023-04423-3
|View full text |Cite
|
Sign up to set email alerts
|

Energy absorption of 2D auxetic structures fabricated by fused deposition modeling

Merve Tunay,
Erhan Cetin

Abstract: Auxetic structures exhibiting unusual mechanical properties from conventional materials are used in many industries and applications due to their high strength, energy absorption performance, high deformation resistance, impact resistance and flexibility. In order to further improve their mechanical properties, it is very important to investigate the deformation behavior and energy absorption characteristics of auxetic structures with different design parameters. In this context, the energy absorption performa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The zigzag infill pattern with a bidirectional raster angle was selected where the raster angles, i.e., the direction of infill lines, of successive layers were ±45°. These parameters were commonly used in similar studies [ 26 ]. The samples were built in the Z-direction, as shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The zigzag infill pattern with a bidirectional raster angle was selected where the raster angles, i.e., the direction of infill lines, of successive layers were ±45°. These parameters were commonly used in similar studies [ 26 ]. The samples were built in the Z-direction, as shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…They observed that the deformation mode of the structure changes significantly by changing the thickness of the cell walls. Tunay et al [ 26 ] investigated the in-plane energy absorption performance of FDM-fabricated re-entrant structures. They found that, among the different design parameters, the thickness of the struts has the highest effect on the energy absorption metrics.…”
Section: Introductionmentioning
confidence: 99%